Peripheral Arterial Interventions with Reduced Contrast Use: The Save Contrast Study - Shammas, Andrew N.; Shammas, Nicolas W.; Shammas, Gail A.; Jones-Miller, Sue (International Journal of Angiology, 2025)
Contrast volume is a predictor of the occurrence of radiocontrast nephropathy and is associated with a high rate of in-hospital mortality and morbidity. Several strategies have been outlined to reduce contrast volume in the angiographic laboratory. Peripheral arterial endovascular procedures can be lengthy and tend to be associated with the use of high volumes of contrast. In this study, we tested specific interventions intended to reduce contrast volume in the angiographic laboratory during peripheral arterial procedures.Fifty consecutive procedures (36 patients) who underwent peripheral arterial interventions at a single center were retrospectively reviewed for demographics, clinical, procedural, and major adverse events (MAE) immediately prior to the implementation of a prospective protocol to reduce contrast use in the angiographic laboratory (group A). Following protocol implementation, 50 additional consecutive procedures (42 patients) were prospectively enrolled (group B). The protocol required diluting contrast concentration to a 2:1 dilution for larger vessels and 3:1 for infrapopliteal vessels, the use of selective injections, digital subtraction angiography, a ruler, road mapping, and intravascular ultrasound. The primary endpoint was acute procedural success, defined as achieving <30% residual narrowing with no intraprocedural complications. A primary safety endpoint was MAE at 30 days, which included unplanned amputation, total mortality, or target lesion revascularization. Descriptive and comparative analyses were performed between the two groups.In groups A and B, 14 and 8 patients had staged procedures, respectively, and were analyzed only once for demographics and clinical characteristics. All patients were analyzed for clinical, angiographic, procedural, and 30-day outcomes. No differences were found in total treated length (mm) or chronic limb-threatening ischemia (p = 0.748). More chronic total occlusions were noted in group B than group A (42.3% vs. 24.2%; p = 0.011). Residual stenosis was significantly more in group B than group A (15.4 ± 23.8% vs. 6.7 ± 6.7%, respectively; p = 0.015). Contrast use was markedly reduced in group B versus group A (90.4 ± 61.3 cc vs. 221.2 ± 84.7 cc, respectively; p < 0.001). MAE were similar in both groups.Contrast use can be significantly reduced during peripheral arterial interventions with the implementation of a few simple measures. A statistically nonsignificant decrease in procedural success and an increase in distal embolizations and perforations were noted in the low contrast group. Larger, randomized studies are needed to determine the overall safety of this low contrast approach in peripheral arterial interventions.
Keywords: contrast; acute kidney injury; radiocontrast nephropathy; peripheral arterial interventions